Determinan Ketahanan Pangan Rumah Tangga di Daerah Pedesaan di Indonesia (Analisis Data Susenas Tahun 2017) - Dilla Syamola; Atik Nurwahyuni (Media Kesehatan Masyarakat Indonesia, 2019)
Food is a basic human need for life while food security is a guarantee for humans to live healthy andproductive work, around 800 million people do not have access to adequate food. Emphasizing food security asan important public health problem. This study uses secondary data from the 2017 National Social Survey (Susenas),this study aims to prove the determinants of household food security in rural areas in Indonesia in 2017.Thecross-sectional study design where data was collected at the same time, and obtained by the Linear Probabilitymodel (LPM) logit and probit models. Estimated results with probit tests show food security is positively relatedto education level, economic status and raskin with estimated coefficients of 0,112, 0.118 and 0,218. The level ofeducation and economic status is significantly related to food security (p value <0,01), but raskin is not significant(p value=0.561). Estimation results show that food security is negatively related to work status, number of familymembers and PKH with estimated coefficients of -0,188, -0,650 and -0,091. Working status, the number of familymembers and PKH are significantly related to food security. Economic status is an important factor for producingquality food in a family.